Predictor of HPV Vaccination Uptake among Foreign-Born College Students in the U.S.: An Exploration of the Role of Acculturation and the Health Belief Model - Fahad T. Alsulami; Jesus Sanchez; Silvia E. Rabionet; Ioana Popovici; Mohamed A. Baraka (Vaccines, 2023)
Objective: to measure the HPV vaccination rate and knowledge about HPV and its vaccine among foreign-born college students; additionally, to measure the effect of acculturation and HBM constructs on the HPV vaccination behavior among foreign-born college students. Methods: a cross-sectional design with a non-probability sample of foreign-born college students was collected via a web-based self-administered survey that measured the HPV vaccination rate, assessed knowledge about HPV and its vaccine, and evaluated the effect of acculturation and HBM constructs on HPV vaccination behavior among foreign-born college students. Results: Foreign-born college students had moderate knowledge about HPV and the HPV vaccine, and about 63% were HPV-vaccinated. Perceived susceptibility, perceived barriers, and cues to action were significantly associated with the HPV vaccination behavior, while knowledge levels about HPV and the HPV vaccine and acculturation levels were not significantly associated with the HPV vaccination behavior of foreign-born college students. Conclusions: The current study shows a moderate vaccination rate and moderate knowledge about HPV and its vaccine among foreign-born college students. Additionally, vaccination campaigns need to increase awareness about the susceptibility to acquiring HPV and minimize the barriers to receiving the vaccine to increase the HPV vaccination rate among foreign-born college students.